The analysis of affordability of medicines with the capillary stabilizing effect in Ukraine - Yaroshenko, A. O.; Shpychak, O. S.; Nazarkina, V. M.; Yakushchenko, V. A.; Buryak, M. V. (Social Pharmacy in Health Care, 2024)
Aim. To analyze the range, price dynamics and affordability indicators of capillary stabilizing medicines at the pharmaceutical market of Ukraine for the period of 2020-2023. Materials and methods. The study object was the indicators of price and consumption of medicines in the group “Angioprotectors” (ATC code C05) within 2020-2023. To analyze the availability of drugs with the capillary stabilizing action presented at the pharmaceutical market of Ukraine, data from the State Register of Medicines of Ukraine, on-line Compendium, as well as data from the drug market research of the “Proxima Research” system, such online resources as Apteki.ua, Tabletki.ua, Liky-control were used. To process the information, we used modern methods of analysis, in particular generalization and systematization of information, comparison and methods of mathematical and statistical calculations. Results. According to the results of the structural analysis of the range of capillary stabilizing medicines in groups C05C A “Bioflavonoids” and C05C X “Other capillary stabilizing medicines”, it was determined that 10 INNs of medicines were registered at the pharmaceutical market of Ukraine. Most of the medicines in the study group (57%) were of domestic production. The medicines analyzed were presented in 9 dosage forms; among them tablets, capsules and gels predominated. Individual and aggregate price indices (PI) for group C05C were calculated, they were: PI 2021/2020 = 1.10, PI 2022/2021 = 1.15, PI 2023/2022 = 1.20. In general, during the study period, price increases were observed by about 50 %, and up to 80 % for individual items. An internal referencing of prices for capillary stabilizing medicines was conducted by 9 reference groups. Prices for medicines in the form of gels and ointments were compared for primary packaging, and for tablets and capsules – per unit of dosage form. The minimum, maximum and average prices in each group and for individual trade names were determined. The analysis of price liquidity indicators (Cliq) showed that most medicines had Cliq in the range from 0.0 to 0.5 or were slightly higher. Corvitin® (BCPP, Ukraine) had the highest solvency adequacy index Ca.s = 0.064. For other medicines of the study group in the form of tablets, capsules, and gels, Ca.s ranged from 0.001 to 0.03. Conclusions. The analysis of the structure of the range of capillary stabilizing medicines at the Ukrainian pharmaceutical market within 2020-2023 has been performed. The indicators characterizing the price situation of these medicines and their affordability for patients have been calculated. According to the results of the study conducted, the indicators of the price liquidity and adequacy of solvency of medicines in this group are in the range of sufficiently high affordability throughout the period analyzed.